Development of Google Sites-Assisted Learning Devices on Vibrations and Waves Material - Sri Susanti Waraga; Tirtawaty Abdjul; Abdul Haris Odja (Postgraduate, University of Mataram, 2023)
Website-assisted learning in science learning can make it easier for students to increase their understanding of knowledge concepts and construct their knowledge based on problems encountered in everyday life to improve learning outcomes. One application that is quite well-known and can be used as a website-assisted learning site is the Google Sites site. Google Sites is a structured application that can easily create websites. Google Sites is an online application launched by Google for creating classes, schools, or other websites. This study aims to determine the quality (validity, practicality, and effectiveness) of the Google Sites Assisted Learning Device on Vibration, Waves, and Sound material. This type of development research refers to the 4-D Model development research consisting of four stages of development, namely Define, Design, Development, and Dissemination. After being validated by two validators, a limited trial was carried out by 58 students consisting of 29 class VIII-A students and 29 class VIII-B at SMP Negeri 1 Kwandang, then the most comprehensive test was carried out by 30 class VIII students at SMP Negeri 2 Kwandang. Data collection techniques in this study used expert validation sheets, student response questionnaires, and student learning outcomes tests. The results of this study indicate that the validation of Google Sites assisted learning devices is included in the â€œValidâ€ category. The practicality of Google Sites helped learning devices is seen from the results of the implementation of learning in class and the student's responses from both trials showing the â€œGoodâ€ category. The Google Sites assisted learning device developed meets the valid, practical, and effective criteria to be suitable for use in science learning in schools.